AI-Driven Personalized Mathematics Learning Through Interactive Mobile Platforms: Effects on Achievement and Motivation - Alkhasawneh, Sani (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Abstract—The increasing use of mobile learning platforms shows that people need adapted experiences that address mobile device features and system capabilities. This research evaluates the powerful effect that mobile learning environments enabled through AI technology would have on mathematics education. The research investigates an AI-based mobile educational platform to enhance students’ mathematics achievement and motivation. The researcher adopted a quasi-experimental approach and selected the participants purposefully, comprising 76 students. The participants were randomly divided into two groups of eleventh grade students. The experimental group consisted of (38) students who were taught mathematics using AI-based mobile educational platform. The control group included (38) students who were taught mathematics using traditional teaching methods. The findings revealed statistically significant differences at the significance level of (α = 0.05) between the mean scores of the experimental and control groups in the post-test. The adjusted mean score of the experimental group was 15.83, compared to 9.49 for the control group, demonstrating the positive impact of AI-based mobile educational platform in enhancing students’ mathematics achievement. The finding confirmed that there are statistically significant differences at the significance level (a = 0.05) between the average ranks of the students in the experimental and control groups on the motivation instrument among high school students due to the use of AI-based mobile educational platform. Based on these findings, the study recommends implementing comprehensive training programs for teachers to ensure the effective integration of AI-based mobile educational platform in the classroom. There is an immediate need for additional studies in this domain, particularly within high schools, to enhance the student’s capacity for self-reliance in skill developmentThe increasing use of mobile learning platforms shows that people need adapted experiences that address mobile device features and system capabilities. This study evaluates the powerful effect that mobile learning environments enabled through artificial intelligence (AI) technology would have on mathematics education. The researcher adopted a quasi-experimental approach. The participants were randomly divided into two groups of eleventh-grade students. The findings revealed statistically significant differences at the significance level of (α = 0.05) between the mean scores of the experimental and control groups in the post-test, demonstrating the positive impact of an AI-based mobile educational platform in enhancing students’ mathematics achievement. The finding confirmed that there are statistically significant differences at the significance level (a = 0.05) between the average ranks of the students in the experimental and control groups on the motivation instrument among high school students. Based on these findings, the study recommends implementing comprehensive training programs for teachers to ensure the effective integration of AI-based mobile educational platforms in the classroom. There is an immediate need for additional studies in this domain, particularly within high schools, to enhance the students’ capacity for self-reliance in skill development.